Humoral immune responses primed by the alteration of gut microbiota were associated with galactose-deficient IgA1 production in IgA nephropathy - Gao, Li; Li, Huixian; Liu, Xiaoling; Li, Haiyun; Li, Peiqi; Lu, Wanhong; Xie, Xinfang; Lv, Jicheng; Jin, Jing (Frontiers in Immunology, 2024)
Galactose-deficient IgA1 (GdIgA1) is critical in the formation of immunodeposits in IgA nephropathy (IgAN), whereas the origin of GdIgA1 is unknown. We focused on the immune response to fecal microbiota in IgAN patients. By running 16S rRNA gene sequencing, we compared IgAN samples to the control samples from household-matched or nonrelated individuals.Levels of plasma GdIgA1 and poly-IgA complexes were measured, and candidate microbes that can either incite IgA-directed antibody response or degrade IgA through specific IgA protease activities were identified. The IgAN group showed distinct composition of fecal microbiota as compared to healthy controls. Particularly, high abundance of Escherichia-Shigella was associated with the disease group based on analyses using Receiver-operating Characteristic (AUC 0.837, 95% CI 0.738-0.914), Principe Coordinates, and the LEfSe algorithm (LDA score: 4.56, p<0.001).Accordingly, the bacterial levels directly correlated with high titers of plasma GdIgA1(r=0.36, p<0.001), and patients had higher IgA1 against stx2(2.88±0.46 IU/ml vs. 1.34±0.35 IU/ml, p=0.03), the main antigen of Escherichia-Shigella. Conversely, the healthy controls showed relatively higher abundance of the commensal bacteria that produce IgA-degrading proteases. Particularly, the abundance of some intestinal bacteria expressing IgA proteases showed an inverse correlation with the levels of plasma GdIgA1 in IgAN. Our data suggest that mucosal IgA production, including those of GdIgA1, is potentially linked to the humoral response to gut Escherichia-Shigella as one of the sources of plasma GdIgA1. Conversely, the IgA protease-producing microbiota in the gut are suppressed in IgAN patients.